Utility of screening for silent myocardial ischaemia in diabetes with an annual electrocardiogram. Issue 3 (14th November 2022) - O'Murchadha, Liam; Egan, Aoife M; Cahill, Kathleen; Flynn, Carly; O'Flynn, Dearbhail; O'Neill, James; Sreenan, Seamus; McDermott, John H
Abstract: Background and Methods: Asymptomatic coronary artery disease (CAD) is common in people with diabetes mellitus, but there is a lack of consensus regarding appropriate screening for the condition. We performed a 12‐lead electrocardiogram (ECG) on 312 consecutive participants with diabetes mellitus attending for routine annual outpatient review in order to determine the effectiveness of a yearly ECG in screening people with diabetes for asymptomatic CAD. Results: Three of 312 participants (0.96%, 95% CI 0.2%–2.78%) had a newly identified ECG abnormality. One person had newly discovered atrial fibrillation. Two people had abnormalities which prompted further investigation for asymptomatic CAD. One of these participants underwent percutaneous coronary intervention. Seventeen further participants had abnormalities on ECG which had been previously documented, the majority having been present since their diagnosis of diabetes. Conclusion: A low positive yield of routine annual ECG in our study does not support its use as a screening tool for asymptomatic CAD in diabetes. Our findings support advice to perform an ECG at diagnosis of diabetes and to repeat only if a person develops relevant symptoms.